School Drug Testing: A Critical Review of the Literature - Daniel T.L. Shek (The Scientific World Journal)
This paper explores the question of whether school drug testing is an effective solution to tackle adolescent substance abuse problems. Research studies in major academic databases and Internet websites are reviewed. Several observations are highlighted from the review: (1) there are few research studies in this area, particularly in different Chinese contexts; (2) the quality of the existing studies was generally low; and (3) research findings supporting the effectiveness of school drug testing were mixed. Methodological issues underlying quantitative and qualitative evaluation studies of the effectiveness of school drug testing are also discussed.